Nodular Scleroderma - Successful Treatment With Extracorporeal Photochemotherapy - Wollina U (Wolters Kluwer Medknow Publications, 2001)
Nodular seleroderma is rare variant of circumscribed scleroderma (morphea). Treatment is often unsatisfactory. This report is on the use of extracorporeal photochemotherapy. A 12 year old girl and a 49 year old woman have been treated once a month on two consecutive days. A complete remission was achieved in one patient after 10 months and an almost complete remission in the young girl after 6 months. The treatment was well-tolerated and no severe side â€" effects occurred. In contrast to previous attempts in treating nodular scleroderma with different modalities, ECP seems to be an effective therapy.